Innovative care for chronic conditions : building blocks for action: global report. - Epping-Jordan, JoAnne (Noncommunicable Diseases and Mental Health, World Health Organization, 2002)
Innovative Care for Chronic Conditions: Building Blocks for Action reports that health care systems around the world must reorganize their health care to meet the rising burden of chronic conditions. It alerts decision-makers throughout the world about these important changes in global health, and presents health care solutions for managing this rising burden. Due to public health successes, populations are ageing and increasingly patients are living with one or more chronic conditions for decades. Urbanization, adoption of unhealthy lifestyles, and the global marketing of health risks such as.